A new kind of stochastic restricted biased estimator for logistic regression model. Issue 9 (4th July 2021) - Alheety, M. I.; Månsson, Kristofer; Golam Kibria, B. M.
Abstract : In the logistic regression model, the variance of the maximum likelihood estimator is inflated and unstable when the multicollinearity exists in the data. There are several methods available in literature to overcome this problem. We propose a new stochastic restricted biased estimator. We study the statistical properties of the proposed estimator and compare its performance with some existing estimators in the sense of scalar mean squared criterion. An example and a simulation study are provided to illustrate the performance of the proposed estimator.